2024
DOI: 10.1186/s43897-024-00090-7
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale analysis of the ARF and Aux/IAA gene families in 406 horticultural and other plants

Shuyan Feng,
Nan Li,
Huilong Chen
et al.

Abstract: The auxin response factor (ARF) and auxin/indole-3-acetic acid (Aux/IAA) family of genes are central components of the auxin signaling pathway and play essential roles in plant growth and development. Their large-scale analysis and evolutionary trajectory of origin are currently not known. Here, we identified the corresponding ARF and Aux/IAA family members and performed a large-scale analysis by scanning 406 plant genomes. The results showed that the ARF and Aux/IAA gene families originated from charophytes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…From a duplication perspective, gene production can be traced to a variety of duplication mechanisms, such as WGD and tandem duplication ( Chen et al, 2023 ; Feng et al, 2024 ). By duplication origin analysis, we found that the seven NLP genes in foxtail millet were derived from dispersed duplication ( Si1G094300.1 , Si2G298700.1 , Si6G248300.1 , Si8G074000.1 , and Si9G553000.1 ) and WGD or segmental duplication ( Si3G084600.1 and Si5G004100.1 ).…”
Section: Discussionmentioning
confidence: 99%
“…From a duplication perspective, gene production can be traced to a variety of duplication mechanisms, such as WGD and tandem duplication ( Chen et al, 2023 ; Feng et al, 2024 ). By duplication origin analysis, we found that the seven NLP genes in foxtail millet were derived from dispersed duplication ( Si1G094300.1 , Si2G298700.1 , Si6G248300.1 , Si8G074000.1 , and Si9G553000.1 ) and WGD or segmental duplication ( Si3G084600.1 and Si5G004100.1 ).…”
Section: Discussionmentioning
confidence: 99%